2009
DOI: 10.1111/j.1750-3841.2009.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins, Antioxidative, and Antimicrobial Properties of American Cranberry (Vaccinium macrocarpon Ait.) and their Press Cakes

Abstract: Amounts of total phenolics, anthocyanins, and ascorbic acid in 4 American cranberry varieties harvested at 4 stages of maturity were measured. The larger amount of phenolic compounds was found in berries of "Black Veil" cultivar (504 mg/100 g) at II stage of maturity. Significantly larger amounts of anthocyanins were determined in the overripe berries of the cultivars "Ben Lear" and "Black Veil." The amount of ascorbic acid in berries increased during ripening from I to III stage, and slightly decreased in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
94
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 20 publications
11
94
2
2
Order By: Relevance
“…The averaged data for different biochemical compounds are presented in Table 1 [32]. Fruits of V. opulus genotypes accumulated on average 2.1 mg/100 g of CC.…”
Section: Biochemical Assaymentioning
confidence: 99%
“…The averaged data for different biochemical compounds are presented in Table 1 [32]. Fruits of V. opulus genotypes accumulated on average 2.1 mg/100 g of CC.…”
Section: Biochemical Assaymentioning
confidence: 99%
“…26 Because NO is an important component of sinonasal innate immunity, 19,27,28 we hypothesized that anthocyanidins may activate sinonasal T2Rs to generate NO. In addition, anthocyanidin-rich plant extracts have antibacterial properties against Staphylococcus aureus, 29,30 Escherichia coli, 29,31 Corynebacterium diphtheria, 32 Moraxella catarrhalis, 32 Bacillus cereus, 33 and Pseudomonas aeruginosa. 34 However, other studies have indicated that anthocyanidins do not have antibacterial effects against B. cereus, 34 E. coli, 34,35 or P. aeruginosa, 30 or that anthocyanidins only reduce inflammation.…”
mentioning
confidence: 99%
“…Several studies have shown that it is both feasible and possibly beneficial to use natural alternatives to nitrates and nitrites. For example plant extracts, including herbs and berries are natural preservatives [24][25][26][27][28]. In addition, Deda et al [29] and have shown a promising example of reducing the nitrite level without compromising the processing and quality characteristics of frankfurter sausages by the addition of tomato paste.…”
Section: Healthy and Safe Alternatives To Nitrates And Nitritesmentioning
confidence: 99%